An agent-based financing model for post-earthquake housing recovery: Quantifying recovery inequalities across income groups. Issue 2 (May 2022) - Alisjahbana, Irene; Moura-Cook, Ana; Costa, Rodrigo; Kiremidjian, Anne
Past disasters have consistently led to unequal housing recovery for different economic groups, in large part, because of the difficulty of obtaining funding for low-income groups. Current earthquake recovery models simplify the financing process for homeowners to rebuild after earthquakes, and in consequence, cannot fully capture disparities in the recovery outcomes of economic groups. In this article, we develop an agent-based financing model for post-earthquake housing recovery. We focus on single-family, owner-occupied homes. The model includes funding from earthquake insurance, the Federal Emergency Management Agency, the Small Business Administration, the Department of Housing and Urban Development, private banks, Non-Governmental Organizations, and personal savings. We present a case study investigating the housing recovery financing in the economically diverse city of San Jose, California, following a hypothetical 7.0 Mw earthquake. By including the financial model in housing recovery simulations, we quantify inequalities in recovery time and total reconstruction completion between income groups. We complement the case study by evaluating several strategies to reduce these disparities and show that a combination of income-targeted funding and redistribution of construction crews can reduce inequalities in regional housing recovery.